Preferencias de canales de youtube en los estudiantes de la Universidad Técnica de Babahoyo 2019 - Vega Reinoso, Alex Santiago (2020)
Currently, the communication industry is advancing by leaps and bounds, the use of technology and the ease of posting videos, has allowed the emergence of a new era in communication where anyone can be a communicator, but this is mainly due to the YouTube platform, which allows the posting of videos for free, with a low level of censorship, it is so framed to this type of communication has appeared the so-called youtubers, who are responsible for posting videos of diverse content, mainly of jocular entertainment. In the country the increase in youtubers is on the rise, first began with the appearance of TV plug. a medium that presented comedy and sketch with the purpose of entertaining, little by little new characters have appeared among the most prominent and accepted by the community are Anthony Swag and Felipe Crespo, who also devote themselves to comedy and make challenges, but really It is being promoted with these spaces or digital channels, because so much public acceptance is the premise of this research, in addition to proposing a better concept to make a true audiovisual content based on communicating something with respect and making videos with better content.